Is there a need for reverse mortgages in Germany? Empirical evidence and policy implications - Florian Bartsch; Florian Buhlmann; Karolin Kirschenmann; Carolin Schmidt (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
Building up sufficient capital for old-age provision often is a challenge for private households. For homeowners, one way to generate old-age income from illiquid housing wealth is the use of equity release products such as home reversion plans or reverse mortgages. However, in Germany the market for reverse mortgages is quasi non-existent. In this policy brief, we provide evidence on the demand- and supply-side reasons for the absence of a reverse mortgage market in Germany, estimate the potential size of and discuss ways how to establish such a market. Using data from financial market expert and household surveys and information from extensive telephone interviews with (former) suppliers of equity release products, we find that uncertainty relating to the homeowner's longevity, moral hazard and adverse selection are the strongest deterrents to reverse mortgage supply. At the same time, the demand-side deterrents are manifold, ranging from product complexity to trust issues and a strong emotional attachment to the home. Estimated market size is very small, but our results suggest that it might grow in the medium term. From a political economy point of view, it might also be worthwhile stimulating the growth of a reverse mortgage market in Germany because it could particularly benefit cash-poor but house-rich households, decreasing old-age poverty.
Keywords: 330; Umkehrhypothek; Private Altersvorsorge; Finanzmarkt; Unvollkommener Markt; Marktgröße; Rentenpolitik; Deutschland